Diagnostics and monitoring of metal-oxide surge arresters in high-voltage networks-comparison of existing and newly developed procedures. - Heinrich, C.
Various diagnostic methods-either on-line or off-line-for monitoring of metal-oxide surge arresters in power systems are known. In most cases they are based on the measurement of the leakage current. This paper describes the most important ones in detail, such as measuring of the V-I-characteristics or analysis of the third harmonic content of the leakage current. Their advantages and weak points, respectively, are discussed, based on the most recent investigation results on the change of the V-I-characteristics due to electrical and nonelectrical stresses. It turns out that almost none of these commonly applied methods really work satisfactorily under either technical or economical aspects. As an alternative the temperature of the MO-insert is proposed to be used for diagnostics purposes. This is made possible by newly developed passive temperature sensors, which can be remotely accessed without any hardware connection to the environment. It is shown how the temperature can be used for monitoring of all kinds of degradation, energy absorption, thermal stability or even pollution performance
Keywords: V-I-characteristics measurement; Economical aspects; Electrical stresses; Energy absorption; High-voltage networks; Leakage current; Leakage current measurement; Metal oxide insert temperature; Metal-oxide surge arresters diagnostics; Metal-oxide surge arresters monitoring; Nonelectrical stresses; Passive temperature sensors; Pollution performance; Power loss; Technical aspects; Thermal stability; Third harmonic content